2021
DOI: 10.1590/1517-8692202127012020_0112
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Public Health Emergencies on the Comprehensive Education of Medical Students in Colleges and Universities From the Perspective of Narrative Medicine

Abstract: The impact of traditional public health emergencies on the comprehensive education of medical students in colleges and universities is mainly reflected in the test of comprehensive literacy. Based on this, this paper studies the construction of a public health emergency impact analysis platform from a medical perspective and cloud computing. From the platform’s database construction, event collection methods, impact evaluation rules and other aspects to achieve accurate analysis of the impact of emergencies, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…According to Oke, Kineber, Albukhari et al and Petri, Rana et al, a feasible construction strategy is importing information to an MS Excel file using the application [46,47]. However, Zhang and Li and Zhao et al found that building employees in an office or any other place may access and use building site materials [48,49]. The cloud storage feature of ad hoc self-service is helpful.…”
Section: Related Literaturementioning
confidence: 99%
“…According to Oke, Kineber, Albukhari et al and Petri, Rana et al, a feasible construction strategy is importing information to an MS Excel file using the application [46,47]. However, Zhang and Li and Zhao et al found that building employees in an office or any other place may access and use building site materials [48,49]. The cloud storage feature of ad hoc self-service is helpful.…”
Section: Related Literaturementioning
confidence: 99%
“…Before the experiment, the students are tested to ensure the validity of the data. After completing the pretest, 60 students were divided into three groups, using [1,15] in the literature and this method for practical teaching. Combined with the measurement of the scale, the learning effect of different groups of students was counted.…”
Section: Experimental Analysismentioning
confidence: 99%
“…Based on Tables 1 and 2, the response time of [1,15], and the method operation in this paper is counted and analyzed. It is regarded as the response time of the system.…”
Section: Experimental Analysismentioning
confidence: 99%
See 2 more Smart Citations